Case report: Multisystem inflammatory syndrome in children associated with COVID-19, macrophage activation syndrome, and incomplete Kawasaki disease - Jesús Javier Martínez-García; Jesús Javier Martínez-García; Jesús Ramon López-Acosta; Daniela Arce-Cabrera; Nidia León-Sicairos; Nidia León-Sicairos; Ana Cristina Hernández-Parra; Hector Melesio Cuen-Diaz; Ricardo Zatarain-Lopez; Adrian Canizalez-Roman; Adrian Canizalez-Roman (Frontiers Media S.A., 2023)
BackgroundMultisystem inflammatory syndrome in children (MIS-C), is a severe complication of coronavirus disease 2019 (COVID-19), characterized by persistent fever, systemic inflammatory response, and organ failure. MIS-C with a history of COVID-19 may share clinical features with other well-defined syndromes such as macrophage activation syndrome, Kawasaki disease, hemophagocytic syndrome and toxic shock syndrome.Case 1An 11-year-old male with a history of hypothyroidism and precocious puberty with positive antibody test for COVID-19 was admitted for fever, poor general condition, severe respiratory distress, refractory shock, and multiple organ failure. His laboratory examination showed elevated inflammatory parameters, and bone marrow aspirate showed hemophagocytosis.Case 2A 13-year-old male with a history of attention deficit hyperactivity disorder and cognitive delay presented clinical manifestations of Kawasaki disease, fever, conjunctival congestion, exanthema, and hyperemia in oral mucosa, tongue, and genitals, with refractory shock and multiple organ failure. Reverse transcriptase polymerase chain reaction (RT-PCR) and antibodies for COVID-19 were negative, inflammation parameters were elevated, and bone marrow aspirate showed hemophagocytosis. Patients required intensive care with invasive mechanical ventilation, vasopressor support, intravenous gamma globulin, systemic corticosteroids, low molecular weight heparin, antibiotics, and monoclonal antibodies and, patient 2 required renal replacement therapy.ConclusionsMultisystemic inflammatory syndrome in children can have atypical manifestations, and identifying them early is very important for the timely treatment and prognosis of patients.